EVALUATING ROAD SAFETY INTERVENTIONS: LESSONS LEARNT FROM THE FIRST 2 YEARS OF A MULTI-COUNTRY APPROACH. (7th October 2012) - Bachani, AM; Hyder, AA; Peden, M; Dipietro, G; Larson, K
Abstract : This workshop focuses on the global road safety interventions project in 10 countries supported by the Bloomberg Philanthropies. Key to the initiative is the demonstration that established interventions on road safety make a significant impact on public health. The project has been running for 2 years, and key lessons have been learnt on defining the epidemiology of road injuries, monitoring the implementation of large-scale programmes on road safety, and assessing the impact of the programmes in an objective and scientific manner. In this regard, three important functions need to be addressed: (1) Defining baseline conditions: a prerequisite for demonstrating any change, a good baseline analysis of road traffic injuries in countries requires a multi-disciplinary review of multiple data sources and strengthening national data systems; (2) Monitoring programme rollout: continuous assessment of a programme through process indicators, and outputs ensure that the operational elements were consistent with the planned programme, and is needed to both identify challenges to implementation and ensure consistency; and (3) Evaluating impact: overall assessment of the change in health, economic and social outcomes due to the implementation of road safety programmes. This approach will have the strengths of: (1) highlighting a core set of methods for each function which have been standardised across all 10 countries; (2) identification of a set of indicators which are scientifically valid and yet practical to measure at country-level for road safety evaluation; and (3) internal consistency across all elements of the evaluation while allowing for flexibility in country-specific approaches.